Analysis of carbon‐14 discharges from Korean nuclear power plants - Hwapyoung Kim; Tae Young Kong; Seongjun Kim; Jinho Son; Changju Song; Jiung Kim; Hee Geun Kim (Energy Science & Engineering)
Abstract The routine practice accompanying the operation of nuclear facilities involves the discharge of radioactive effluents from nuclear power plants (NPPs). Regulation of this discharge to the environment hinges on three criteria: radioactivity concentration, public dose, and radioactivity. Among these, radioactive carbon‐14 holds particular significance as it possesses an extensive half‐life of 5730 years, making it a primary source of radiation dose to communities residing around NPPs. In Korea, the monitoring of carbon‐14 discharges from pressurized water reactors (PWRs) in gaseous effluents has been ongoing since 2012, whereas before 2012, monitoring exclusively focused on carbon‐14 discharges from pressurized heavy water reactors (PHWRs). Analysis of carbon‐14 discharges from Korean PHWRs indicates that their emission constituted less than 1% of total radioactive effluents over the past two decades. In the context of Korean PWRs, carbon‐14 discharge monitoring was absent from 2002 to 2011, resulting in an absence of data regarding such discharges during that period. After introducing carbon‐14 discharge monitoring in gaseous effluents from Korean PWRs, emissions from 2012 to 2021 contributed 3% of the total gaseous effluents. These findings indicate that despite being the primary contributor to public dose, carbon‐14 discharges from NPPs constitute a minor portion of the radioactive effluent discharge.